Toxicology, pharmacology and therapy of animals poisoned by anticoagulant rodenticides: a review - Kanivets, N.; Kravchenko, S.; Dmytrenko, N.; Deviatko, O.; Kulynych, S.; Deleichuk, O. (Scientific Progress & Innovations, 2025)
One of the problems that has existed for many years and is the cause of death of domestic dogs and cats is poisoning associated with the consumption of rodenticides (zoocides). The purpose of the study was to conduct a broad review of world scientific publications on the toxicodynamics of rodenticides of the anticoagulant group, the pharmacology of specific antidotes and methods of their use in the treatment regimen for domestic dogs and cats. The results of the analysis of the modern world literature on the arsenal of anticoagulant rodenticides are highlighted, their toxicodynamics and pathogenesis of pathological processes caused by the action of these agents are described, the literature on the expediency and effectiveness of the use of certain pharmacological agents as antidotes is systematized, and modern treatment regimens for domestic dogs and cats with rodenticide-anticoagulant poisoning are analyzed. It has been established that the vast majority of rodenticides used in practical use against mouse-like rodents are of two groups: hydroxycoumarin derivatives of the first and second generations and indandione derivatives. Poisoning of dogs and cats by second-generation anticoagulants (brodifacoum) accounts for 27.6 %. The basis of the toxicodynamics of all rodenticides described in this article is the disruption of vitamin K recycling, which leads to the inactivation of blood coagulation factors II, VII, IX and X, as well as the inhibition of endogenous vitamin K epoxy reductase, which makes the carboxylation reaction impossible. The nonspecificity of the first clinical manifestations of rodenticide-anticoagulant action leads to late diagnosis of poisoning, which increases the mortality of pets during treatment. Clinical studies should be supplemented by the results of blood tests (hypochromic anemia, neutrophilia with leukocytosis, ESR increase, MCV decrease, increased fibrinogen content) against the background of prothrombin activity disorders) and radiological findings (pleural effusion in 63.6 %, retroperitoneal effusion in 28.6 % and peritoneal effusion in 14.3 % of poisoned animals). Pathognomonic pathologic signs are internal bleeding and massive hemorrhagic diathesis. Treatment should be based on the use of vitamin K1 in high doses (1.5–5 mg/kg). Other forms of vitamin K are ineffective. The conducted literature analysis allows us to understand the global trend in the use, toxicodynamics and pharmacotherapy of dogs and cats for rodenticide poisoning, which makes it possible to increase the effectiveness of combating animal poisoning.